Case Report: Emphysematous Cystitis and Pyelonephritis Induced by Uterine Prolapse in a Subject With Untreated Diabetes Mellitus - Iwamoto, Hideyuki; Anno, Takatoshi; Takenouchi, Haruka; Takahashi, Kaio; Horiya, Megumi; Kimura, Yukiko; Kawasaki, Fumiko; Kaku, Kohei; Tomoda, Koichi; Uehara, Shinya; Kaneto, Hideaki (Frontiers in Medicine, 2021)
Type 2 diabetes mellitus (T2DM) is often accompanied by a lot of complications due to chronic hyperglycemia and inflammation. Emphysematous cystitis and pyelonephritis are rare types of urinary tract infections and are often complicated with DM. Herein, we report a case of emphysematous cystitis and pyelonephritis complicated with untreated DM. In addition, this case was very rare and interesting in that her emphysematous cystitis and pyelonephritis were induced by severe uterine prolapse, obstructive uropathy and urination disorders. Both uterine prolapse and DM should be appropriately treated because both can lead to the development of emphysematous cystitis and pyelonephritis.